Cycle Time Estimation of a Multiple Product Production Line: An Approach With Fuzzy and Chance-Constrained Programming - Xu, Min; Abdul-Kader, Walid; Ganjavi, Ozhand (INFOR. Information systems and operational research, 2009)
This paper presents an approach to estimate the cycle time of a multi-product production line composed of workstations that are subject to random failure and repair. We utilize chance constrained programming (CCP) to establish an upper bound for the stochastic variables and approximate them with interval variables. Fuzzy linear programming (FLP) is utilized to incorporate the interval variables into the optimization model. We discuss and utilize some of the existing methods of determining production line efficiency as the line efficiency is a component of our proposed model. Numerical examples are presented and the results obtained by the modeling approach are then compared and validated with simulation results.